New PRPS1 variant p.(Met68Leu) located in the dimerization area identified in a French CMTX5 patient - Lerat, Justine (Mol Genet Genomic Med, 2019)
BACKGROUND: CMTX5 is characterized by peripheral neuropathy, early‐onset sensorineural hearing impairment, and optic neuropathy. Only seven variants have been reported and no genotype‐phenotype correlations have yet been established. PRPS1 has a crystallographic structure, as it is composed of three dimers that constitute a hexamer. METHODS: Next‐generation sequencing (NGS) was performed using a custom 92‐gene panel designed for the diagnosis of Charcot‐Marie‐Tooth (CMT) and associated neuropathies. RESULTS: We report the case of a 35‐year‐old male, who had presented CMT and hearing loss since childhood associated to bilateral optic neuropathy without any sign of retinitis pigmentosa. A new hemizygous variant on chromosomic position X:106,882,604, in the PRPS1 gene, c.202A > T, p.(Met68Leu) was found. This change is predicted to lead to an altered affinity between the different subunits in the dimer, thereby may prevent the hexamer formation. CONCLUSION: CMTX5 is probably under‐diagnosed, as an overlap among the different features due to PRPS1 exists. Patients who developed polyneuropathy associated to sensorineural deafness and optic atrophy during childhood should be assessed for PRPS1.